Vertebral osteomyelitis with profound neurologic deficit : successful treatment with rhBMP-2 and titanium cage device - Sembrano, Jonathan N.; Yson, Sharon C.; Polly, David W. Jr.
The efficacy of bone morphogenetic proteins (BMP) in infection has not yet been established. Since fusion is a necessary aim in the treatment of vertebral osteomyelitis with spinal instability, BMP may be a helpful adjunct in the surgical treatment of these cases. We present a case of vertebral osteomyelitis associated with neurologic deficits, treated with decompression and fusion using recombinant human bone morphogenetic protein-2 (rhBMP-2) and titanium cage device. Eradication of infection, recovery of neurologic deficits, spinal stabilization and solid fusion were achieved and maintained at 5 years follow-up.
In: Acta Medica Philippina, 2012 vol 46 (2) pages: 69-73
Keywords: Bone Morphogenetic Proteins; Osteomyelitis